Non-viral TRAC-knocked-in CD19KICAR-T and gp350KICAR-T cells tested against Burkitt lymphomas with type 1 or 2 EBV infection: In vivo cellular dynamics and potency - Braun, Tobias; Pruene, Alina; Darguzyte, Milita; vom Stein, Alexander F.; Nguyen, Phuong-Hien; Wagner, Dimitrios L.; Kath, Jonas; Roig-Merino, Alicia; Heuser, Michael; Riehm, Lucas L.; Schneider, Andreas; Awerkiew, Sabine; et al. (Frontiers in Immunology, 2023)
Introduction The ubiquitous Epstein–Barr virus (EBV) is an oncogenic herpes virus associated with several human malignancies. EBV is an immune-evasive pathogen that promotes CD8+ T cell exhaustion and dysregulates CD4+ T cell functions. Burkitt lymphoma (BL) is frequently associated with EBV infections. Since BL relapses after conventional therapies are difficult to treat, we evaluated prospective off-the-shelf edited CAR-T cell therapies targeting CD19 or the EBV gp350 cell surface antigen. Methods We used CRISPR/Cas9 gene editing methods to knock in (KI) the CD19CAR.CD28z or gp350CAR.CD28z into the T cell receptor (TCR) alpha chain (TRAC) locus. Results Applying upscaled methods with the ExPERT ATx® MaxCyte system, KI efficacy was ~20% of the total ~2 × 108 TCR-knocked-out (KO) generated cells. KOTCRKICAR-T cells were co-cultured in vitro with the gp350+CD19+ BL cell lines Daudi (infected with type 1 EBV) or with Jiyoye (harboring a lytic type 2 EBV). Both types of CAR-T cells showed cytotoxic effects against the BL lines in vitro. CD8+ KICAR-T cells showed higher persistency than CD4+ KICAR-T cells after in vitro co-culture with BL and upregulation of the activation/exhaustion markers PD-1, LAG-3, and TIM-3. Two preclinical in vivo xenograft models were set up with Nod.Rag.Gamma mice injected intravenously (i.v.) with 2 × 105 Daudi/fLuc-GFP or with Jiyoye/fLuc-GFP cells. Compared with the non-treated controls, mice challenged with BL and treated with CD19KICAR-T cells showed delayed lymphoma dissemination with lower EBV DNA load. Notably, for the Jiyoye/fLuc-GFP model, almost exclusively CD4+ CD19KICAR-T cells were detectable at the endpoint analyses in the bone marrow, with increased frequencies of regulatory T cells (Tregs) and TIM-3+CD4+ T cells. Administration of gp350KICAR-T cells to mice after Jiyoye/GFP-fLuc challenge did not inhibit BL growth in vivo but reduced the EBV DNA load in the bone marrow and promoted gp350 antigen escape. CD8+PD-1+LAG-3+ gp350KICAR-T cells were predominant in the bone marrow. Discussion The two types of KOTCRKICAR-T cells showed different therapeutic effects and in vivo dynamics. These findings reflect the complexities of the immune escape mechanisms of EBV, which may interfere with the CAR-T cell property and potency and should be taken into account for future clinical translation.